Supply Chain Sustainability Modeling and Innovative Research Frameworks - Mangla, Sachin K.; Ram, Mangey (De Gruyter series on the applications of mathematics in engineering and information sciences ;, 2021)
Supply chains are significant in improving business efficiency. Sustainable supply chains help industries enhance their ecological, monetary, and social performance. Innovative research frameworks as well as the modelling of sustainability issues are significant to different stakeholder's perspectives. This book guides researchers and practitioners through developing effective sustainable supply chains to meet UN Sustainable Development Goals (SDGs).